The level of interference of english learners’ mother tongue with their learning of prepositions: case of English Composition II students of the Foreign Language Department at the University of El Salvador, semester I- 2013 - Martínez Abrego, Claudia Guadalupe
The purpose of this research is focused on determine the level of interference of English learners’ mother tongue with their learning of English prepositions. Learning English as a foreign language is not an easy process, and Spanish native speakers have their issues. In terms of second language teaching and learning, transfer is the influence of the learner´s native language in a second language. Clearly, it may take time to master a language where students need to organize their knowledge into appropriate coherent structures, in this case the correct use of English prepositions. English composition II students, of the Foreign Language Department at the University of El Salvador are not making the exception of this phenomenon, in this research the group of researchers found out the common errors students have when using English prepositions.